THE CORRELATION BETWEEN STUDENTS' REWRITING OF THE STORY IN FILM AND THEIR VOCABULARY MASTERY(A CORRELATION STUDY IN THE SECOND GRADE OF MTS NURUL FALAH) - Dian Anggraini, - (2008)
The research was intended to investigate the correlation between students' rewriting of the story in film and their vocabulary mastery (A Correlation Study in the Second Grade of MTs Nurul Falah, Cimahi). This research was conducted to find out the way to improve students' vocabulary mastery through watching film and rewrite the story about it. For that purpose, the method used in this research was quantitative method. The sample was second grade of junior high school students, which was collected by using random sampling technique. The instruments used in this research were writing test and vocabulary test. The students' scores on writing and vocabulary are computed using Pearson Product Moment. Based on statistical analysis by using computation analysis, SPSS (Statistical Product and Service Solutions) verse 15.0, the coefficient correlation or rcounted equals to 0.784 and rtable equals to 0.361. Since the rcounted > rtable, it means that the correlation between students' writing of the story in film (X) and vocabulary mastery (Y) was significant. Given the above result, the findings could be summarized that generally there is significant correlation between students' rewriting of the story in film and their vocabulary mastery. In conclusion, students could use the vocabulary in film better after they watched the film and rewrite the story about it. Furthermore, the writer suggests that it is time to use film as a media in improving students' rewriting ability and their vocabulary mastery.